Comparison of stress contributing factors based on teaching experience among secondary school physical education teachers in Selangor, Malaysia - Mohd Khairudin, Ab Wahid; Soh, Kim Geok; Soh, Kim Lam; Ong, Swee Leong (Wolters Kluwer - Medknow, 2021)
Objective: This study identified stress contributing factors among secondary school physical education teachers and compared them based on teaching experience. Research Methodology: This study adopted a cross-sectional study design, and the data were obtained using the survey method. This study involved 258 physical education teachers within the secondary level of public schools. The questionnaire consisted of five constructs: career dilemma, career progression, misconceptions of career, work environment and work relationship. The teaching experience was divided into four categories of 1–5 years, 6–10 years, 11–15 years and 16 years above. Descriptive statistical analysis and one-way ANOVA were used to describe the findings. Findings: Three main contributing stressors among physical education teachers were career dilemma (mean [M] = 35.26, standard deviation [SD] = 5.17), development status (M = 34.77, SD = 4.48) and work relationship (M = 27.09, SD = 2.87). Factors contributing to stress based on teaching experience found that misconceptions of careers showed a significant result where F value (3, 254) = 3.95, p = 0.009 < 0.05. Tukey's post hoc analysis found that significant results were reported teaching experience between 1–5 and 6–10 years. Conclusions: It was evident that teaching experience had a major influence in determining the stress level among teachers. Teaching experience assisted teachers in decision-making, which leads to better handling of stressful situations. In addition, this study observed a misconception in a career as one of the contributing factors of stress experienced by the teachers with a teaching experience of 1–5 and 6–10 years who took part in this study.